Combining user preferences and expert opinions: a criteria synergy-based model for decision making on the Web - Karanik, Marcelo Javier; Bernal, Rubén Alfredo; Peláez-Sánchez, José Ignacio; Gómez-Ruiz, José Antonio (Springer-Verlag, 2019)
Customers strongly base their e-commerce decisions on the opinions of others by checking reviews and ratings provided by other users. These assessments are overall opinions about the product or service, and it is not possible to establish why they perceive it as good or bad. To understand this “why”, it is necessary an expert’s analysis concerning the relevant factors of the product or service. Frequently, these two visions are not coincident and the best product for experts may not be the best one for users. For this reason, trustworthy decision-making methods that integrate the mentioned views are highly desirable. This article proposes a multi-criteria decision analysis model based on the integration of users’ preferences and experts’ opinions. It combines the majority’s opinion and criteria synergy to provide a unified perspective in order to support consumers’ ranking-based decisions in social media environments. At the same time, the model supplies useful information for managers about strengths and weaknesses of their product or service according to users’ experience and experts’ judgment. The aggregation processes and synergy criteria are modeled in order to obtain an adequate consensus mechanism. Finally, in order to test the proposed model, several simulations using hotel valuations are performed.
Keywords: Toma de decisiones; Decision making; Multi-criteria decision analysis; Criteria coalition synergy; Majority aggregation; Social media